(untitled) (Mustansiria Dental Journal, 2018)
This in vitro study evaluated the effect of glass ionomer liner in limiting temperature rise during composite curing with Light Emitting Diode (LED cure unit) compare it with Conventional visible light-cure lamp. Twenty sound upper premolar teeth were used & on the buccal and palatal surfaces of them, a standardized class V cavity was prepared, 1mm occlusal to the cemento-enamel junction. Cavity dimensions of occluso-gingival height 1.5mm, mesio-distal width of 3mm. The depth of the cavity was 2mm and was calibrated by measuring with a pre marked periodontal probe. The teeth were randomly divided into four groups according to the cure mode and filling teqnique. Each group consist of 5 teeth (10 cavities); Group I; each cavity filled with 2mm (micro-hybrid resin composite) and cured with Quartz Tungsten Halogen light unit (QTH), Group II; the same as Group I but cured with Light Emitting Diod (LED cure unit), Group III; each cavity filled with glass ionomer lining of 0.5mm and 1.5mm (micro-hybrid resin composite), and cured with Quartz Tungsten Halogen light unit (QTH), & Group IV; each cavity filled with glass ionomer lining of 0.5mm and 1.5mm (micro-hybrid resin composite) but cured with Light Emitting Diod (LED cure unit). Temperature was measured before light curing of the composite resin & immediately after it. Then the Temperature was measured by a type K thermocouple. The results revealed that there were significant differences between the groups at p<0.01 with in favor of the group filled with composite resin & cured with LED with glass ionomer lining. The use of sandwich restorations with LED curing unit produced lesser temperature degrees toward the pulp space.